2013
DOI: 10.1016/j.indcrop.2012.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steeping variables and substrate mesh size on starch yield extracted from oil palm trunk

Abstract: Large area of oil palm plantation in Malaysia generated significant amount of oil palm biomass such as oil palm trunk. This material is assumed to possess multipurpose utilization, including a starch-producing raw material. This work is aimed to determine the total extractable starch from oil palm trunk (OPT) using commercial steeping methods. The extraction methods used in this study include steeping the OPT in sodium metabisulphite (Na2S2O5) alone and with the addition of lactic acid (C3H6O3). The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…The steeping method used water as solvent in order to extract the native starch. Dried grated material (sago trunk) of 2 g according to the grade sizes (2.80 mm, 2.00 mm, 1.00 mm, 0.85 mm, 0.45 mm, 0.30 mm and <0.30 mm) were steeped in 0.2% sodium metabisulphite (Na 2 S 2 O 5 ) (Tay et al, 2013) which was dissolved in water (H 2 O) at room temperature as shown in Figure 2. The steeping period was set at 5 mins, 24 hrs, 48 hrs and 72 hrs.…”
Section: Starch Extraction Using Steeping Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The steeping method used water as solvent in order to extract the native starch. Dried grated material (sago trunk) of 2 g according to the grade sizes (2.80 mm, 2.00 mm, 1.00 mm, 0.85 mm, 0.45 mm, 0.30 mm and <0.30 mm) were steeped in 0.2% sodium metabisulphite (Na 2 S 2 O 5 ) (Tay et al, 2013) which was dissolved in water (H 2 O) at room temperature as shown in Figure 2. The steeping period was set at 5 mins, 24 hrs, 48 hrs and 72 hrs.…”
Section: Starch Extraction Using Steeping Methodsmentioning
confidence: 99%
“…The extracted liquids were centrifuged at 2000 rpm for 10 mins and analyzed to determine the value of starch content using VIS spectrophotometer (Lambda 35, Perkin Elmer, USA) at 650 nm wavelength. An iodine solution was added into the solution as a starch indicator (Tay et al, 2013). The experiments were repeated six times.…”
Section: Starch Extraction Using Steeping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EFB is believed to have the potential for converting carbohydrates into different biochemical with the high content of cellulose and hemicelluloses (about 75 %). Biochemical conversion uses biocatalysts, such as enzymes, in addition to heat and other chemicals, to convert the carbohydrate portion of the biomass (hemicellulose and cellulose) into an intermediate sugar stream (Tay et al 2013). These sugars are intermediate building blocks that can then be fermented or chemically catalyzed into a range of advanced biofuels and value-added chemicals.…”
Section: Biochemical Derivatives (Using Hydrolysis and Fermentation Tmentioning
confidence: 99%
“…In 2012, total area of oil palm plantations located in Malaysia and Indonesia exceeded 10 million hectares. Since during harvesting each hectare yields over 70 tones of dry waste trunk biomass (Chin et al 2012), the resource seems to be cheap, abundant and promising prospective raw material for chemical processing to sugars, alcohols and other derivatives (Akmar and Kennedy 2001; Tay et al 2013;Chin et al 2010;Wanrosli et al 2004). Alternatively, palm trunk can be used as a source of lignocellulosic material for wood technology in particleboard (Baskaran et al 2013), plywood (Hoong et al 2013), furniture (Suhaily et al 2012) or laminated veneer lumber (Sarmin et al 2013).…”
Section: Introductionmentioning
confidence: 99%